Exosomes derived from human umbilical cord mesenchymal stem cells protect against cisplatin-induced ovarian granulosa cell stress and apoptosis in vitro - Liping Sun (Nature Portfolio, 2017)
Abstract Human umbilical cord mesenchymal stem cells (huMSCs) can treat primary ovarian insufficiency (POI) related to ovarian granulosa cell (OGC) apoptosis caused by cisplatin chemotherapy. Exosomes are a class of membranous vesicles with diameters of 30–200 nm that are constitutively released by eukaryotic cells. Exosomes mediate local cell-to-cell communication by transferring microRNAs and proteins. In the present study, we demonstrated the effects of exosomes derived from huMSCs (huMSC-EXOs) on a cisplatin-induced OGC model in vitro and discussed the preliminary mechanisms involved in these effects. We successfully extracted huMSC-EXOs from huMSC culture supernatant and observed the effective uptake of exosomes by cells with fluorescent staining. Using flow cytometry (with annexin-V/PI labelling), we found that huMSC-EXOs increased the number of living cells. Western blotting showed that the expression of Bcl-2 and caspase-3 were upregulated, whilst the expression of Bax, cleaved caspase-3 and cleaved PARP were downregulated to protect OGCs. These results suggest that huMSC-EXOs can be used to prevent and treat chemotherapy-induced OGC apoptosis in vitro. Therefore, this work provides insight and further evidence of stem cell function and indicates that huMSC-EXOs protect OGCs from cisplatin-induced injury in vitro.